Hubungan antara Fase Merangkak dan Kemampuan Pragmatik Anak Usia Prasekolah di TK Dharma Wanita Nambakan Kediri - Notiviara, Anisa; Aditya Setyawan, Dodiet; Laela Abida, Liza (Politeknik Kesehatan Kemenkes Surakarta, 2023)
Abstract Background: Gross motor skills greatly affect the development of children. If a child experiences motor delays, then the child will experience developmental and growth delays (Permana, 2013). In minimizing errors in meaning (miss understanding), children need to develop pragmatic aspects so that their language skills develop properly (Sari, 2021). Objective: This study aims to determine the relationship between the crawling phase and pragmatic abilities in preschool-age children at Dharma Wanita Nambakan Kindergarten, Kediri. Method: This type of quantitative research with a cross sectional design. The data collection technique uses total sampling with a sample of 30 respondents. The data that has been collected will be analyzed univariately and bivariately using the Spearman Rank statistical test. Research Outcome: Based on the results of Spearman's Rank analysis test, the value of ρ (sig.) is 0.036 or the value of ρ (sig.) < 0.05, then Ha (alternative hypothesis) is accepted, indicating that there is a relationship between the paying phase and children's pragmatic abilities. The strength of the correlation or relationship between the two variables is in the range of 0.2 to < 0.4, which is included in the weak category. Conclusion: There is a relationship between the crawling phase and the pragmatic abilities of preschoolers at Dharma Wanita Nambakan Kindergarten, Kediri. Keywords: Crawling Phase, Pragmatic Ability, Preschool Aged Children